Bioluminescence-Based Method for Measuring Assimilable Organic Carbon in Pretreatment Water for Reverse Osmosis Membrane Desalination - Weinrich, Lauren A. (American Society for Microbiology (ASM), 2011)
A bioluminescence-based assimilable organic carbon (AOC) test was developed for determining the biological growth potential of seawater within the reverse osmosis desalination pretreatment process. The test uses Vibrio harveyi, a marine organism that exhibits constitutive luminescence and is nutritionally robust. AOC was measured in both a pilot plant and a full-scale desalination plant pretreatment.